POLITICAL PARTIES AND ELECTORAL REFORMS: GIVING INDIA'S UNCERTAIN DEMOCRACY A CHANCE TO SURVIVE (NATIONAL CAPITAL LAW JOURNAL, 2003)
NA
Keywords: Political Parties; Electoral Reforms; Parliamentary Federal System; Presidential System; Party System Decline; Anti-Defection Law; Election Commission of India; Federalism; Coalition Governments; Developmental State Crisis